Pathological complete remission of a locally advanced gastric cancer by neoadjuvant therapy “sandwich” regimen as SOXAP+ fluorescence laparoscopic surgery +SOXAP: Case report - Ma, Yanling; Wang, Bofang; Maswikiti, Ewetse Paul; Wang, Xueyan; Wang, Na; Chen, Hao (Frontiers in Pharmacology, 2022)
Gastric cancer is an extremely burdensome and challenging malignant tumor with a high incidence and a high mortality rate, which seriously results in a thorny prognosis for oncology patients. Surgical treatment combined with postoperative adjuvant therapy are currently the most regular methods for the treatment of locally advanced gastric cancer（LAGC）, but long-term efficacy is not an ideal outcome. Therefore, herein we report a case of a pathologically confirmed complete remission of LAGC treated by the administration of neoadjuvant therapy combined with fluorescence laparoscopic surgery with more significant long-term survival. With that being mentioned, a 60-year-old man was diagnosed as moderately differentiated gastric antrum adenocarcinoma (T3N1M0). Moreover, after 3 cycles of SOXAP regimen (Oxaliplatin+S-1+Apatinib+ Camrelizumab), and it was found out that the gastric lesion was smaller in size than before, total laparoscopic radical resection of the distal gastric cancer was performed at the time. Furthermore, no tumor cells were seen in gross specimen post operatively, achieving complete remission of the case. In addition, he also underwent 3 cycles of SOXAP regimen postoperatively. Interestingly and assuredly, he was in good health after an almost 2-year follow up period. These results suggest that this therapeutic regimen is a promising treatment modality for the management of locally advanced gastric cancers.